Percutaneous endoscopic gastrostomy with jejunal extension plus percutaneous endoscopic gastrostomy (PEG-j plus PEG) in patients with gastric/duodenal cancer outlet obstruction - Fonseca, Jorge (2015)
"Background – Stent palliation is the gold standard for gastric/duodenal cancer outlet obstruction. When stenting is impossible, feeding may be achieved through a gastrojejunostomy (PEG-J), but displacement of jejunal tube is frequent due to manipulation for feeding and drainage. Gastric outlet obstruction results on increased gastroesophageal reflux or extra-tube leakage. In order to reduce the jejunostomy tube manipulation and the gastric residuum, we created a second gastrostomy (PEG) dedicated to gastric drainage, reducing the PEG-J handling. Objective – Our aim was evaluating of the usefulness of an added second gastrostomy in a PEG-J patient, for: 1. controlling symptomatic reflux and extra-tube leakage; 2. preventing jejunal tube dislocation. Methods – We retrospectively evaluated patients were stent palliation of gastric/duodenal cancer outlet obstruction was not achieved, who were referred and underwent PEG-J. We selected four of these patients who needed a second PEG dedicated to gastric drainage, which was performed a few centimetres apart from the gastrojejunostomy. In order to achieve an efficient gastric drainage and provide the maximum comfort to the patient, the drainage PEG tube could be linked to an ileostomy bag. Results – The four PEG-J cancer patients with longer survival developed symptoms associated with an important gastric residuum. After the drainage gastrostomy, symptoms subsided or vanished and there were no jejunal tube dislocations. Conclusions – When stenting is not possible in patients with gastric/duodenal outlet obstruction due to cancer growing, feeding PEG-J plus drainage PEG may be an alternative, allowing duodenal/jejunal feeding and gastric drainage with minimal manipulation of the jejunal tube."